2015
DOI: 10.1007/s13593-015-0303-4
|View full text |Cite
|
Sign up to set email alerts
|

Metaheuristics for agricultural land use optimization. A review

Abstract: Agricultural landscapes presently cover about 46 % of earth terrestrial surface. This cultivated area is decreasing, whereas the global food demand is projected to increase up to 70 % in 2050. The intensification of agriculture is not a solution to this food issue because intensive agriculture has often resulted in pollution and loss of biodiversity. On the other hand, mechanistic models with optimization algorithms can be used to design alternative land uses for sustainable agriculture. Here, we present a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 107 publications
0
54
0
Order By: Relevance
“…Selecting the appropriate analysis tool for a particular issue is a difficult decision, as many authors have confirmed, both when talking about multi-criteria decision theories [30] and metaheuristic techniques [31]. To sum up, as it was stated: "There is no method that is universally best or even applicable for all situations."…”
Section: Introductionmentioning
confidence: 99%
“…Selecting the appropriate analysis tool for a particular issue is a difficult decision, as many authors have confirmed, both when talking about multi-criteria decision theories [30] and metaheuristic techniques [31]. To sum up, as it was stated: "There is no method that is universally best or even applicable for all situations."…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated the effectiveness of this algorithm through representation of optimal solutions with different priority and better application of non-linear objective functions in comparison to linear functions. Memmah et al (2015) presented a review of 38 case studies about land use optimization using metaheuristics. Some of their conclusions are as follows: "the success of metaheuristics is problem-dependent and a future challenge is the use of parallelization techniques along with the hybridization of different metaheuristics or of metaheuristics with other optimization methods".…”
Section: Introductionmentioning
confidence: 99%
“…Models of soil preservation dealing with both ecological and economic objectives have already been developed, e.g., see Dogliotti, Rossing, and van Ittersum (2004) and Seppelt and Voinov (2002), for multiparcel management, and Memmah, Lescourret, Xin, and Lavigne (2015) for a review of different modeling approaches. Here, we apply tools developed in the framework of viability theory based on set valued analysis and mainly devoted to the control of dynamic systems with constraints.…”
Section: Introductionmentioning
confidence: 99%